ANALISIS WATAK TOKOH DALAM BUKU KUMPULAN CERPEN GADIS PEMIMPI KARYA TATI KUSMIATI - Putri, Nur Febriani Arphiani (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2025)
The purpose of this study is to describe the character in the book Short Story Collection of Dreaming Girls by Tati Kusmiati. The reason why the researcher took the title is because short stories are literary works that raise the reality of people’s lives and contain moral messages carried out by the characters through the character of the characters played. This research is a qualitative descriptive research. To obtain data, the researcher used a read-note technique. The technique of character analysis of the researcher’s character uses content analysis (content analysis) of intrinsic elements, namely the character character, in short stories.From the results of the analysis, it was found that the character of the antagonist (ambitious, justifying all means and arrogant) and the character of the protagonist (honest. Independent, defender, humble, clever and generous) in the short story collection Girl Dreamer by Tati Kusmiati.